Preoperative immunonutrition and carbohydrate loading associated with improved bowel function after radical cystectomy. (26th April 2021) - Patel, Sephalie Y.; Trona, Nathaniel; Alford, Brandon; Laborde, Jose M.; Kim, Youngchul; Li, Roger; Manley, Brandon J.; Gilbert, Scott M.; Sexton, Wade J.; Spiess, Philippe E.; Poch, Michael A.
Abstract: Background: Preoperative malnourishment has been consistently associated with poor outcomes after radical cystectomy and other major abdominal surgeries. Most enhanced recovery after surgery (ERAS) studies have examined preoperative nutrition and its relationship to outcomes after gastrointestinal surgery. Although numerous studies have demonstrated the benefits of using an ERAS protocol, this study in unique in comparing 2 ERAS protocols, with and without a nutrition component. Methods: A formalized preoperative nutrition protocol (PNP) recommending use of preoperative immunonutrition and carbohydrate drink was introduced in June 2018. A total of 78 consecutive patients who drank both beverages were compared with 92 historical controls. Multivariable logistic regression analyses were sequentially performed to determine if preoperative nutrition was associated with binary outcome variables (30‐day complication, infectious complication, and readmission within 30 days). Results: The preoperative nutrition group and control group were statistically similar in distribution of age, sex, American Society of Anesthesiologists physical status classification, clinical stage, and body mass index. Return of bowel function was found to occur earlier in the preoperative nutrition group than in the control group (3.12 vs 3.74 days; relative risk, 0.82; CI, 0.73–0.93; P = .0029). Complications within 30 days were similar in both groups (63.6% vs 55.4%; P = 0.36). Infectious complications (42.9% vs 37%; P = .53) and readmission within 30 days (22.1% vs 15.2%; P = .34) were also similar in both groups. Conclusions: Use of a PNP including immunonutrition and carbohydrate drink may be associated with earlier return of bowel function after radical cystectomy.